Dynamic Ocular Surface and Lacrimal Gland Changes Induced in Experimental Murine Dry Eye - Xiao, Bing (PLoS One, 2015)
Dry eye disease can be a consequence of lacrimal gland insufficiency in Sjögren’s Syndrome or increased tear film evaporation despite normal lacrimal gland function. To determine if there is a correlation between severity effects in these models and underlying pathophysiological responses, we compared the time dependent changes in each of these parameters that occur during a 6 week period. Dry eye was induced in 6-week-old female C57BL/6 mice by exposing them to an Intelligently Controlled Environmental System (ICES). Sixty mice were housed in ICES for 1, 2, 4 and 6 weeks respectively. Twelve were raised in normal environment and received subcutaneous injections of scopolamine hydrobromide (SCOP) 3 times daily for 5 days. Another sixty mice were housed in a normal environment and received no treatment. Corneal fluorescein staining along with corneal MMP-9 and caspase-3 level measurements were performed in parallel with the TUNEL assay. Interleukin-17(IL-17), IL-23, IL-6, IL-1, TNF-α, IFN-γ and TGF-β2 levels were estimated by real-time PCR measurements of conjunctival and lacrimal gland samples (LGs). Immunohistochemistry of excised LGs along with flow cytometry in cervical lymph nodes evaluated immune cell infiltration. Light and transmission electron microscopy studies evaluated LGs cytoarchitectural changes. ICES induced corneal epithelial destruction and apoptosis peaked at 2 weeks and kept stable in the following 4 weeks. In the ICES group, lacrimal gland proinflammatory cytokine level increases were much lower than those in the SCOP group. In accord with the lower proinflammatory cytokine levels, in the ICES group, lacrimal gland cytosolic vesicular density and size exceeded that in the SCOP group. ICES and SCOP induced murine dry eye effects became progressively more severe over a two week period. Subsequently, the disease process stabilized for the next four weeks. ICES induced local effects in the ocular surface, but failed to elicit lacrimal gland inflammation and cytoarchitectural changes, which accounts for less dry eye severity in the ICES model than that in the SCOP model.